Validitas Media Ulang HAKI (Ular Tangga Hak dan Kewajiban) pada Materi Hak dan Kewajiban Siswa Kelas V Sekolah Dasar - Irsada Gos Salim; Iis Daniati Fatimah; Ina Agustin (GRM Academic Press, 2026)
This study aims to develop a learning medium called ULANG HAKI (Snake and Ladder of Rights and Obligations) for teaching the topic of rights and obligations to fifth-grade elementary school students. The research employed the Research and Development (R&D) approach using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The development process began with identifying students’ learning needs and classroom problems, followed by designing and producing the learning medium, validating the product through expert judgment, and evaluating its feasibility. The research subjects included one material expert, one media expert, and one language expert who assessed the quality and appropriateness of the developed product. Data were collected through classroom observations, teacher interviews, and expert validation questionnaires. The collected data were analyzed using descriptive quantitative techniques by calculating percentage scores to determine the validity level of the learning medium. The validation results showed that the ULANG HAKI learning medium achieved a score of 88% from the material expert, 100% from the media expert, and 96% from the language expert. These findings indicate that the developed medium falls into the highly valid category and is suitable for implementation in Civic Education (PPKn) learning. Furthermore, the medium offers curriculum-aligned content, attractive visual design, clear instructions, and language that is appropriate for elementary school students. As an interactive game-based learning medium, ULANG HAKI has the potential to increase students’ learning motivation, classroom participation, critical thinking, and understanding of the concepts of rights and obligations, thereby creating a more engaging and meaningful learning experience.